Mild Hyperhomocysteinemia and Hemostatic Factors in Patients with Arterial Vascular Diseases - Freyburger, G; Labrouche, S; Sassoust, G; Rouanet, F; Javorschi, S; Parrot, F (Thrombosis and Haemostasis, 1997)
Mild hyperhomocysteinemia, due to genetic or to environmental factors, is now recognized as a risk factor for premature arterial disease, including peripheral arterial occlusion, thrombotic stroke and myocardial infarction. It is defined by either an increased level of fasting homocysteine or by an increased level after loading with methionine, which is more frequently altered than the former. We studied the hemostatic parameters in 88 patients with premature arterial disease (mean age 43 ± 11 years). We confirmed previously known hemostatic alterations described in vascular patients when compared to controls, but found that, among patients, some of these parameters were more altered in hyperhomocysteinemic patients. When fasting homocysteine was increased, higher alterations were found in factors VIIIc, von Wille- brand and thombin-antithrombin complexes were more elevated. When post-methionine load homocysteine was increased, alterations in fibrinolytic parameters were more pronounced.